2014
DOI: 10.1007/s00213-014-3510-9
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of acute or chronic administration of ovarian hormones on the effects of desipramine in the forced swim test in female rats

Abstract: Rationale Gender may influence antidepressant (AD) treatment outcome. In order to address this pre-clinically, the potential effects of ovarian hormones on AD treatment in ovariectomized female rats were investigated. Objectives In the first study, the effect of acute administration of estrogen and progesterone on the antidepressant-like effects of desipramine (DMI), a selective norepinephrine reuptake inhibitor (SNRI), was investigated in the forced swimming test (FST). In the second study, the effect of ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…However, estrogen injection was associated with a decrease of 5-HT levels and an increased 5-HT turnover rate (Pandaranandaka et al, 2006), or showed no differences in OVX female rat (Lu et al, 1998). It is worth to note that most of the estrogen-dependent changes of 5-HT-related depressive behaviors in animals were associated with estrogen administration acutely or chronically (Shah and Frazer, 2014) which might be different from endogenous estrogen in related to the serotonergic system (Pandaranandaka et al, 2009). Instead of treating animals with exogenous estrogen, studies of 5-HT metabolism in female animals at young, middle and old ages demonstrated that young female animals exhibited higher hippocampal 5-HT concentration than middle-age animals (Kiss et al, 2012), and women over 60 years of age had less platelet 5-HT content than younger age (Guicheney, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…However, estrogen injection was associated with a decrease of 5-HT levels and an increased 5-HT turnover rate (Pandaranandaka et al, 2006), or showed no differences in OVX female rat (Lu et al, 1998). It is worth to note that most of the estrogen-dependent changes of 5-HT-related depressive behaviors in animals were associated with estrogen administration acutely or chronically (Shah and Frazer, 2014) which might be different from endogenous estrogen in related to the serotonergic system (Pandaranandaka et al, 2009). Instead of treating animals with exogenous estrogen, studies of 5-HT metabolism in female animals at young, middle and old ages demonstrated that young female animals exhibited higher hippocampal 5-HT concentration than middle-age animals (Kiss et al, 2012), and women over 60 years of age had less platelet 5-HT content than younger age (Guicheney, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Absent or paradoxical responses to fluoxetine (Li et al, ; Pic‐Taylor et al, ) or other antidepressants (Ribeiro et al, ; Thelen, Sens, Mauch, Pandit, & Pitychoutis, ) were previously observed in female rats. Sexual hormones may impact the responses of female rats to fluoxetine (Benmansour, Weaver, Barton, Adeniji, & Frazer, ; Craft, Kostick, Rogers, White, & Tsutsui, ; de Oliveira et al, ; De Vry, Maurel, Schreiber, De Beun, & Jentzsch, ; Enríquez‐Castillo et al, ; Estrada‐Camarena, López‐Rubalcava, Hernández‐Aragón, Mejía‐Mauries, & Picazo, ; Estrada‐Camarena, Rivera, Berlanga, & Fernández‐Guasti, ; Flores‐Serrano et al, ; Gomez et al, ; Li et al, ; Lifschytz, Shalom, Lerer, & Newman, ; McNamara et al, ; Mitic, Simic, Djordjevic, Radojcic, & Adzic, ; Molina‐Hernández & Téllez‐Alcántara, , ; Pic‐Taylor et al, ; Récamier‐Carballo, Estrada‐Camarena, Reyes, & Fernández‐Guasti, ; Sell et al, ; Shah & Frazer, ). Indeed, ovariectomized rats, with or without estrogen replacement, presented male‐like response to fluoxetine in the FST (Benmansour et al, ; Estrada‐Camarena et al, ; Estrada‐Camarena et al, ; Gomez et al, ; Molina‐Hernández & Téllez‐Alcántara, , ; Récamier‐Carballo et al, ; Sell et al, ; Shah & Frazer, ) while intact females continue to display no response (Pic‐Taylor et al, ) or paradoxical response (Li et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The single publication on the effect of desipramine on FST behaviors in freely cycling rats measured the behaviors of Wistar rats during daily 5-min swims for 42 consecutive days in a shallow FST chamber, and a scoring system incompatible with the standard modified method (Contreras, Martínez-Mota, & Saavedra, 1998). The literature that has differentiated between active behaviors in the FST has consistently reported significantly more climbing behaviors elicited by desipramine (Detke et al, 1997; Shah & Frazer, 2014; Slattery & Cryan, 2012). Although most of the studies reporting increased climbing used subacute dosing (three doses in 24 hours prior to testing), one used a chronic dosing regimen with a final dose given 30 min prior to testing (Detke et al, 1997), and another used a chronic dosing regimen via osmotic pump (Shah & Frazer, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Desipramine, a standard tricyclic antidepressant, was used as a positive control to evaluate the predictive validity of the aCRS model. Desipramine’s antidepressant effect is primarily attributed to blockade of the norepinephrine reuptake transporter (NET) and has been associated with increased climbing behaviors in the FST in male (Detke et al, 1997; Slattery & Cryan, 2012) and ovx rats (Shah & Frazer, 2014). Desipramine (Sigma-Aldrich, St. Louis, MO) dissolved in 0.9% NaCl (saline) was given subcutaneously (SC) at a dose of 5 mg/kg.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation